Development of the CINTA-DLT Teacher Training Model to Integrate Deep Learning and Love-Based Curriculum at MTs Al Ikhwan Banjarmasin Using the Plomp Model - Septy Rovana; Ahmad Suriansyah; Aslamiah Aslamiah (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to develop and validate the CINTA-DLT Teacher Training Model (CINTA–Deep Learning Training) to support deep learning and a love-based curriculum in madrasas. The study employed an Educational Design Research (EDR) approach using the Plomp development model with five stages. The participants consisted of five teachers from MTs Al Ikhwan Banjarmasin and three expert validators, and the instruments included interviews, validation sheets, practicality questionnaires, and observations. The data were analyzed using interactive qualitative analysis and the Aiken's V validity test. The results showed an Aiken's V value of 0.90 (very valid) and a practicality score of 90% (very practical). Qualitatively, the model improved teachers' understanding of deep learning, internalization of love-based values, pedagogical skills, and professional motivation and reflection. The CINTA-DLT Model comprises five main phases—Connecting Meaning, Internalization, Nurturing Practice, Transformation, and Affirmation—forming a holistic, value-based, reflective, and practice-oriented teacher training framework. Therefore, the CINTA-DLT Model is considered feasible as a humanistic teacher training model aligned with the 2025 Madrasah Curriculum.